Annual report 2015 - (:unkn) unknown (Publications Office of the European Union, 2016)
Cedefop's annual report is intended as a presentational and accountability tool which can help stakeholders and the general public to understand Cedefop's priorities and specific objectives, its main output and outcomes of its work. The issue 2015 gives an overview of Cedefop's key achievements in 2015. This year "has been marked by a number of events that will inevitably have an impact on the immediate future of Cedefop and European vocational education and training (VET). The celebration of Cedefop's 40th anniversary, the Riga conclusions and the renewed ET 2020, the internal reorganisation of the Centre and its planning for the new cycle 2017-20 have given it a new lease of life and more vigour to work harder for VET." (Editor, BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; I 1.5 Internationale Organisationen & Institutionen; I 2.2 Europa; CEDEFOP; Berufsbildungsforschung; EU-Bildungspolitik; Europäische Union; 2015